Scaffolding self-regulated problem solving: the influence of content-independent metacognitive prompts on students’ general problem-solving skills - Jasper, Leonie; Melle, Insa (Technische Universität Dortmund, 2025)
The ability to solve problems is considered a key competence in today’s society. However, solving domain-specific problems, such as those in chemistry, places high demands on students. Effective problem solving requires metacognitive strategies and their corresponding ‘cold’ executive functions, namely working memory and cognitive flexibility, which many students struggle with. To support students, we developed a web-based tool, ChemApro, designed to scaffold problem-solving processes by providing content-independent metacognitive prompts. The tool was used over several weeks in seven schools with N = 153 participating students (M age = 15.63, SD = 0.79) in grades 10 and 11. Among other things, the study focuses on ChemApro’s effect on students’ general problem-solving skills, and on how students perceive the tool in terms of its attractiveness and usability. In line with the study results, the use of ChemApro was descriptively associated with greater improvements in the treatment group’s problem-solving skills compared to the corresponding baseline, particularly among those students with a lower cognitive level. However, the mixed ANOVA did not reveal significant interaction effects between group and time, although trends in the low cognitive level group approached significance. Additionally, students rated the tool’s attractiveness and usability as moderate.
Chemistry teacher international; 7(4)
Keywords: self-regulated problem solving; metacognitive strategies; executive functions; scaffolding; ECRICE 2024; 540